The Application of Plant Proteases from Garlic (Allium sativum) for Biomonitoring of Heavy Metals in the Environment (Asian Journal of Plant Biology, 2014)
In this work, a novel source of protease for the bioassay of heavy metals has been developedusing proteases extracted from garlic (Allium sativum). The principle of casein-Coomassie-dyebinding assay has been applied for this purpose. The optimum concentration of enzyme andsubstrate were determined at 0.7 mg/mL and 0.175 mg/mL, respectively. The crude proteases ofAllium sativum exhibited optimal activity at pH 6.0, temperature at 40oC and incubation time of60 minutes. The IC50 values for mercury, copper, cadmium, nickel and chromium were 0.0590mg/L, 0.6398 mg/L, 1.291 mg/L, 0.9865 mg/L and 1.871 mg/L, respectively. The calculatedlimits of quantitation (LOQ) value for mercury, copper, cadmium, nickel and chromium were0.0188 mg/L, 0.025 mg/L, 0.50 mg/L, 0.10 mg/L and 0.5 mg/L, respectively. The calculatedLOD values for mercury, copper, cadmium, nickel and chromium were 0.0002 mg/L, 0.006mg/L, 0.05 mg/L, 0.02mg/L and 0.1 mg/L, respectively. The crude proteases extracted fromAllium sativum showed good potential for the development of a rapid, sensitive, and economicinhibitive assay for the biomonitoring of mercury, copper, cadmium, nickel and chromium inthe environments.
Keywords: garlic (Allium sativum), proteases, iomonitor, heavy metals